Level of knowledge and practice among nurses regarding patients’ safety post Percutaneous Coronary Intervention (PCI) - Mohd Jubri, Nursyakirah; Ruslan, Rusila (IIUM Press, 2025)
Background: Percutaneous Coronary Intervention (PCI) is a common and critical procedure that uses a minimally invasive approach to unblock coronary arteries and restore blood flow to the heart. Nurses play a vital role in post-PCI care yet gaps in knowledge and practice may affect patient safety. This study was conducted to assess the level of knowledge and practice among nurses regarding patient safety post-PCI at Sultan Ahmad Shah Medical Centre @IIUM (SASMEC @IIUM), Kuantan, Pahang, Malaysia. Methods: This was a quantitative cross-sectional study involving 98 nurses from Cardiac Care Unit (CCU) and Medical Wards of SASMEC @IIUM. Data were collected using a printed questionnaire covering sociodemographic, knowledge, and practice. The data were analysed using descriptive statistics and Chi square test. Results: Out of 79 nurses surveyed, 59.5% (n=47) demonstrated good knowledge, and 63.3% (n=50) demonstrated adequate practice regarding patient safety post-PCI. A significant association was found between knowledge and practice levels (????²=6.986, p=0.008), indicating that nurses with better knowledge were more likely to demonstrate adequate practice. However, no significant associations were found between knowledge or practice levels and sociodemographic factors such as age, gender, or years of experience. Conclusion: The study demonstrated a significant positive association between nurses’ knowledge and their practice related to patient safety post-PCI, underscoring the pivotal role of knowledge in enhancing clinical performance. Although sociodemographic factors such as age, gender, and years of experience showed no significant associations, the findings highlight the necessity of structured professional development initiatives to strengthen nursing competency and uphold patient safety standards following PCI